Understanding how reed-biochar application mitigates nitrogen losses in paddy soil: Insight into microbially-driven nitrogen dynamics. (May 2022) - Zhang, Yuping; Zhao, Hang; Hu, Wang; Wang, Yizhe; Zhang, Hanfeng; Zhou, Xuan; Fei, Jiangchi; Luo, Gongwen
Abstract: Biochar application to chemical-amended paddy soils has been proposed as a potential strategy to enhance nitrogen (N) retention and nitrogen use efficiency (NUE) by crops. However, optimal concentrations for these enhancements and the potential drivers are not well understood. Herein, a column-based pot experiment was carried out to investigate the impacts of reed-biochar application rate on N losses and dynamics in paddy soils treated by chemical fertilizer, and particularly, to explore the dominant factors of the processes. The addition of 2–4% reed-biochar had the most significant effects on mitigating N loss by leaching. Reed-biochar amendment increased soil total N and mineral N (NH4 + -N and NO3 − -N) content, and denitrifying gene abundance, and the increments of those variables were positively related to the application rate. Soil treated with 1–4% reed-biochar at harvest period showed higher gene abundances of ammonia-oxidizing and dissimilatory nitrate reduction to ammonium (DNRA) and higher activity of β-1, 4-N-acetyl-glucosaminidase (NAG) and leucine aminopeptidase compared with the 4–8% application rate. The amoA -AOA gene abundance, NAG activity, and total carbon (C) content were the main predictors of total N and mineral N accumulated leakage. Total C content was the main predictor of soil total N and mineral N content, followed by the pH and NAG activity. These results suggest that adding 2–4% reed-biochar was more beneficial to mitigate N loss and thus enhance soil N storage and availability. This study highlights the importance of understanding how microbial populations mediate N transformation to decipher biochar-driven NUE enhancement in paddy soils. Graphical abstract: Image 1 Highlights: Nitrogen loss and N dynamics of paddy soil were related to reed-biochar addtion rate. Adding 2%–4% reed-biochar was more beneficial to reduce N loss and enhance N retention. Abundance of ammonia oxidizing and denitrifying gene was higher in biochar treatment. amoA -AOA abundance, NAG activity, total C content were mian predictors of N leakage. Total C content was mian predictor of soil N retention, followed by pH and NAG activity.